Parental Involvement and Academic Achievement: Voices of Role-Players in Secondary Schools in Mpumalanga, South Africa - Ndwandwe, Ntokozo Dennis (Research in Social Sciences and Technology, 2023)
Parents are broadly acknowledged to be essential partners in the schooling process of their children, with parental involvement being linked to positive impact on academic achievement. Regrettably, poor parental involvement remains significate and an unfortunate challenge in South African schools, as well as a contributing factor to high failure rates in schools. Therefore, this study investigated the relationship between parental involvement and the academic achievements of learners in secondary schools in the Ehlanzeni District, Mpumalanga, using Epstein’s theory of overlapping spheres of influence as a theoretical lens. A qualitative research design underpinned by the interpretive paradigm was employed, using a sample of two secondary schools with a purposive sample of principals, teachers and parents. Data for the study was obtained through semi-structured interviews conducted with the principals and through focus group discussions conducted with teachers and parents, respectively. The data was gathered through thematic analysis approach. The findings obtained reveal that parental involvement improves discipline and learner achievement. However, various factors hindered parent involvement, such as the lack of confidence in providing assistance to children with homework, conflicts in home–school scheduling, ineffective communication, and reluctance to attend parent meetings and to serve on governance structures. The study recommends that both teachers and parents should establish good home–school relationships, teacher training for parent involvement should be organised, with schools developing a parent involvement programme, so that a viable collaborative partnership can be established between school and home.